Making Technology More Intelligent: Seeking the "Local Characteristics" of Digital Rural Governance - Wan, Hongling (International Journal of Social Sciences and Public Administration, 2026)
Digital rural governance is the cornerstone of modernizing national governance, therefore exploring digital rural governance has become an important topic. The "locality" of digital countryside refers to the need to pay attention to the uniqueness of rural society, and to break through a single operating mode in the interaction between modern and traditional. As an efficient governance tool, digital technology can help rural development, but it cannot be limited to universal linear processes. It should be embedded in the natural environment, social status, and core needs of rural areas, and closely integrate technology with the characteristics and practices of rural areas. Only then can technology truly empower rural areas. On the premise of respecting the development laws of different types of rural areas, a basic path for the "locality" of digital rural areas is constructed through typical cases to promote the modernization process of digital rural governance.